PENGGUNAAN NATRIUM SIKLAMAT PADA ES LILIN BERDASARKAN PENGETAHUAN DAN SIKAP PRODUSEN DI KELURAHAN SRONDOL WETAN DAN PEDALANGAN KOTA SEMARANG (Natrium Cyclamate on the Ice Candle Based on the Producer’s Knowledge in Srondol Wetan and Pedalangan, Semarang) - Retno Purwaningsih; Rahayu Astuti; Trixie Salawati (Universitas Muhammadiyah Semarang, 2010)
Sodium Cyclamate is an artificial sweetener that is often used. Sodium cyclamate could be carcinogenic. The use of sodium cyclamate in Indonesia regulated in a No 722/MenKes/Per/IX/88 Permenkes RI and RI Permenkes no.208/MenKes/Per/IV/85 about usage limits for each food product. The data of BBPOM Semarang in 2007 found sodium cyclamate in food snacks (student of primary school) including ice candle. The purpose of this study is to measure the use of sodium cyclamate at ice candle producers based on knowledge and attitudes about the content of sodium cyclamate.. This research is explanatory with the survey method. The population is all the ice candle producers in Srondol Wetan and Pedalangan, as many as 25 producers. Samples were tested in the laboratory ice candle BB POM Semarang. Data analysis using Spearman rank correlation test. The results showed the level of knowledge of respondents 'good' by 16.0%, the category of